Antagonism of chemokine receptor CXCR3 inhibits osteosarcoma metastasis to lungs - Pradelli, Emmanuelle (2009)
Metastasis continues to be the leading cause of mortality for patients with cancer. Several years ago, it became clear that chemokines and their receptors could control the tumor progress. CXCR3 has now been identified in many cancers including osteosarcoma and CXCR3 ligands were expressed by lungs that are the primary sites to which this tumor metastasize. This study tested the hypothesis that disruption of the CXCR3/CXCR3 ligands complexes could lead to a decrease in lungs metastasis. The experimental design involved the use of the CXCR3 antagonist, AMG487 and 2 murine models of osteosarcoma lung metastases. After tail vein injection of osteosarcoma cells, mice that were systematically treated with AMG487 according to preventive or curative protocols had a significant reduction in metastatic disease. Treatment of osteosarcoma cells in vitro with AMG487 led to decreased migration, decreased matrix metalloproteinase activity, decreased proliferation/survival and increased caspase-independent death. Taken together, our results support the hypothesis that CXCR3 and their ligands intervene in the initial dissemination of the osteosarcoma cells to the lungs and stimulate the growth and expansion of the metastatic foci in later stages. Moreover, these studies indicate that targeting CXCR3 may specifically inhibit tumor metastasis without adversely affecting antitumoral host response.